Roxadustat, a HIF-PHD inhibitor with exploitable potential on diabetes-related complications - Fang, Tingting; Ma, Congcong; Zhang, Zhanming; Sun, Luning; Zheng, Ningning (Frontiers in Pharmacology, 2023)
Diabetes mellitus (DM) is a group of metabolic diseases caused by absolute or relative deficiency of insulin secretion and characterized by chronic hyperglycemia. Its complications affect almost every tissue of the body, usually leading to blindness, renal failure, amputation, etc. and in the final stage, it mostly develops into cardiac failure, which is the main reason why DM manifests itself as a high clinical lethality. The pathogenesis of DM and its complications involves various pathological processes including excessive production of mitochondrial reactive oxygen species (ROS) and metabolic imbalance. Hypoxia and related HIF(hypoxia-inducible factor) signaling pathway play an important role in both of the above processes. Roxadustat is an activator of HIF-1α, which increases the transcription of HIF-1α by inhibiting hypoxia-inducible factor prolyl hydroxylase (HIF-PHD). Roxadustat shows regulatory effects on maintaining metabolic stability in the hypoxic state of the body by activating many downstream signaling pathways such as vascular endothelial growth factor (VEGF), glucose transporter protein-1 (GLUT1), lactate dehydrogenase (LDHA), etc. This review summarizes the current research findings of Roxadustat on the major complications, including retinal damage, cardiovascular disease, nephropathy, atherosclerosis, and impaired wound healing, which are all induced by diabetes.